(untitled) (Al Dzahab, 2025)
Purpose: This study aims to analyze the potential elements of gharar and riba in the operational mechanisms of electronic money and their implications for the validity of transactions from the perspective of Islamic economics in Indonesia. The rapid development of digital payment systems requires comprehensive studies regarding the compliance of modern financial instruments with Sharia principles, particularly the prohibitions against riba and gharar. Design/methodology/approach: This research employs a qualitative approach with juridical-normative and conceptual research types. The data used are secondary data obtained through literature studies, including the Qur’an, hadith, fatwas issued by the National Sharia Council of the Indonesian Ulema Council, regulations related to electronic money, and relevant scientific literature. The analysis is conducted using a descriptive-analytical method by identifying the operational mechanisms of electronic money, examining the contract structures used, and assessing the potential emergence of gharar and riba elements in practice. Findings: The results indicate that, in principle, electronic money can be considered Sharia-compliant as long as it fulfills the requirements of clear contractual arrangements, transparency of information, and the absence of riba. The potential for gharar may arise in the form of unclear contractual terms, lack of transparency in administrative fees, refund mechanisms, and system risks that are not proportionally communicated to users. Meanwhile, the potential for riba may occur if float funds are positioned as a qardh contract and utilized commercially without a Sharia-compliant mechanism, or if additional schemes resembling interest are applied. Research implications: The findings suggest that the validity of electronic money transactions from the perspective of Islamic economics largely depends on the clarity of contractual agreements, accountable fund management, system transparency, and effective Sharia supervision. Therefore, electronic money providers need to ensure that their operational mechanisms align with Sharia principles to enhance the trust of Muslim consumers and support the development of an ethical and Sharia-compliant digital financial ecosystem.